Pengaruh Penggunaan Media Scrapbook Terhadap Kemampuan Menulis Teks Biografi Pada Siswa – Siswi Kelas X SMK Negeri 3 Medan - Rajagukguk, Risnauli; Saragih, Elza Leyli Lisnora; Wulan, Eka Putri Saptari (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to determine the effect of scrapbook media on the ability to write biographical texts of Grade X students at SMK Negeri 3 Medan in the 2025/2026 academic year. The research applied a quantitative method with a one group pretest-posttest experimental design. The population consisted of 432 students, while the sample was 36 students from class X RPL 1 selected using Cluster Random Sampling. Data were analyzed through normality (F-test), homogeneity, and hypothesis testing. The results showed that the mean pretest score was 59.44 (SD = 12.63) and the mean posttest score was 67.67 (SD = 7.96). The t-test at a 0.05 significance level indicated thitung > ttabel (0.1784 < 1.695), leading to the rejection of H0 and acceptance of Ha. The data were also normally distributed and homogeneous. Thus, scrapbook media significantly improves students’ ability to write biographical texts